LEXICAL MEANS EXPRESSING THE CONCEPT OF "FRIENDSHIP" IN UZBEK AND ENGLISH - Akhmedova Tursunoy Bakhtiyarovna (The Conference Hub, 2025)
The article discusses the spiritual development of the history of human society, national-cultural values, their place in the history of mankind. The special place of manifestations of universal human values, concepts such as life and death, good and evil, goodness and evil in human society is emphasized. The expression of the axiological concept of “Friendship” in Uzbek “Do‘stlik” through lexical means is analyzed. Common and distinctive features in the expression of the concept of “Friendship” are distinguished. It is shown that lexical units, along with providing information, perform a stylistic and semantic function.
Keywords: Concept, axiological concept, linguistic unit, lexical means, lexeme, meaning, word, sema, national-cultural sema, valence, own meaning, portable meaning.